Aplikasi Metode Nilai Hasil (Earned Value Method) pada Sistem Pengendalian Proyek - Siti Yuliani Pujihastuti; Mandiyo Priyo (Semesta Teknika, 2012)
In a project implementation, the project implementer wants the project completed on time as efficient as possible while the produced quality is in accordance with the initial plan. Therefore, in order to meet the requirements for controlling process and to minimize any deviations that can occur during the project, the earned value method is considered accurate. The aim of this study was to identify the final result of the project which will be achieved in the aspect of cost (whether the project experience gains, losses, or within budget) and time (whether the project is delayed, ended early, or on time as scheduled). The study was conducted on the 4th, 8th, 12th, 16th, and 20th weeks by using the earned value. Earned Value Method, or often called the Concept of Earned Value, is the concept of calculating project costs in accordance with the budget and the scope of job which have been completed or implemented (budgeted cost of works performed). This method combines the cost, schedule, and work performance of a project. Therefore, this method is considered effective in monitoring and controlling project activities.